PENGARUH CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR BARANG KONSUMSI DAN PERDAGANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Debora Ratih Hartantri; Saarce Elsye Hatane (Business Accounting Review, 2017)
The purpose of this study was to know the influence of corporate governance to financial distress. Firm Size and Leverage was added as control variable. CG was measured by using board size, board meeting and board composition. Financial distress measured by using dummy variable coded 1 if the firm was considered as distressed and 0 in other case. The samples used in this study were 44 companies in the sector of consumer goods and trade ( listed in Indonesian Stock Exchange) period of 2010-2015. The hypothesis was tested by using logistic regression analysis. The result of this study revealed that board size and firm size significant and negative influenced on financial distress. Beside that, Leverage significant and positive influenced on financial distress. However, board composition and board meeting, had no significant influence on financial distress.